Studi Pemanfaatan Dana Bantuan Operasional Kesehatan (BOK) Terhadap Penurunan AKI/AKB Di Kota Bandar Lampung Tahun 2019 - Dian Utama Putri; William Arisandi (Jurnal Ilmu Kesehatan Masyarakat Indonesia (JIKMI), 2020)
AbstractHealth Operational Aid (BOK) had been utilized for the implementation of promotive and preventive services. This included maternal and child health improvement in the primary healthcare centers of Kudus district health office work area. However, maternal and child mortality in Bandar Lampung city tended to increase. The study objective was to explain the utilization of Health Operational Aid in the maternal and child health improvement efforts in the primary healthcare centers of Bandar Lampung public health office. This was a qualitative study. This study compared utilization of BOK in high absorbing primary healthcare centers that succeeded in minimizing maternal and infant mortality cases and in low absorbing primary healthcare centers that did not succeed in minimizing maternal and infant mortality cases. Data were collected through in-depth interview to main informants namely the head of primary healthcare centers, and triangulation informants namely maternal and child health coordinator midwives and head of Bandar Lampung public health office. Content analysis was applied in the data analysis. Results of the study showed that in the high absorbing primary healthcare centers that succeeded in minimizing cases: understanding about health operational aid technical guideline was clear; implementation of activities was according to the reports; executors were involved in a plan of action formulation; and there was an evaluation on the activity implementation. In addition, in the success primary healthcare centers, it was found that executors of the activities arranged the completeness of supporting data; therefore, report making was not done only by the management team of primary healthcare center’ health operational aid. To be successful in the health operational aid utilization for maternal and child health, application of a right management function in the primary healthcare center is needed. This management function includes planning, implementation and evaluation. Key words: utilization study, health operational aid, decrease in maternal and infant mortality rates , public health office.